Proposed health service zones : health-related housing and infrastructure in Northern Territory Aboriginal communities - Hoffmann, Ben.; Bailie, Ross.; Cooperative Research Centre for Aboriginal and Tropical Health (Australia) ([Darwin] : Cooperative Research Centre for Aboriginal and Tropical Health, 2001)
The final of three reports of a detailed analysis of data from the second Community Housing and Infrastructure Needs Survey (CHINS 1999); health-related community infrastructure - public facilities and amenities, water and electricity supply, sewerage and drainage, health services and dwellings; presents data for larger communities within 21 health services zones that are proposed for the planning and delivery of primary health care services; maps indicate the location of areas of need within each health service zone.
"November 2001."
Includes bibliographic references (p. 77).
Keywords: Aboriginal Australians -- Health and hygiene -- Northern Territory; Aboriginal Australians -- Services for -- Northern Territory; Aboriginal Australians -- Housing -- Northern Territory; Communications - Telecommunications; Water supply; Health services; Housing; Education; Community development - Infrastructure and municipal services; Transport; Northern Territory (NT)